Predisposing, Enabling, and Reinforcing Factors Influencing Punctuality of Initial Pregnancy Visits - Titi Maharrani; Evi Yunita Nugrahini (Aloha International Journal of Health Advancement (AIJHA), 2018)
Introduction: Health services for pregnant mother is given by the health workers and must qualifying the minimum standard. Assessment for implementation of health services could be remained through acquisition of K1 and K4. This research is supposed to see how predisposing, enabling and reinforcing factors influence the punctuality of initial pregnancy visits. Methods: This analytical research with Cross Sectional design took a place at PMB in North Surabaya Region with total sample as much as 101 person using stratified random sampling technique. Independent variables on this research are predisposing, enabling and reinforcing factors, while the dependent variable is accuracy of initial pregnancy visit. The data obtained by questionnaire and analyzed by Logistic Regression Test. Result: The result of Logistic Regression Test obtain at parity variable p value 0.001, education p 0.0004, distance p value 0.004 and husband support p value 0.000. while at income variable obtained p value 0.540 or p value > 0.05. This is interpreted that parity, education, distance and husband support significantly affect the accuracy of initial pregnancy visit, but not with income variable. Conclusion: Statistically, reinforcing factors affect the punctuality of initial pregnancy visit more significant compared with predisposing and enabling factors. Keywords: Predisposing Factors, Enabling Factors, Reinforcing Factors, Pregnancy visit.